Early Prediction of Alzheimer’s Disease Using OCT Imaging Technique - C S Sandeep; Kumar A Sukesh; Mahadevan K; P Manoj (Journal of Alzheimer's Research and Therapy, 2019)
Alzheimer’s Disease (AD) is one amongst the overwhelming types of dementia that distresses the brain nerve cells leading to a perpetual loss in memory and creating a lot of difficulties for the family members in caretaking. The prediction of the disease at an earlier stage is a common problem. The most prevalent imaging modalities used for diagnosing AD are Magnetic Resonance Imaging (MRI), Positron Emission Tomography (PET) and Single Photon Emission Computed Tomography (SPECT). They can provide valuable information regarding the changes in internal and external brain regions and activities for diagnosing AD. But the relevant studies made on retina reveals that in addition to brain changes there are some variations on the retina layers of the AD patients. Therefore, the retina can be used as a biomarker for diagnosing AD. There are different techniques available for an eye examination. Most noticeable of them are Fundus Imaging and Optical Coherence Tomography (OCT). In this paper, we have focused on OCT retinal images of AD patients for the early diagnosis of AD.
Keywords: Alzheimer’s Disease